The Conflict Between the Principle of State Sovereignty and the Enforcement of International Criminal Court Judgments - Sharifi Ziraksar, Hussain; Razawifard, Behzad; Kamran, Hussain Dad; Tariq Wamiq, Mohammad (International journal of multicultural and multireligious understanding, 2025)
The conflict between the principle of state sovereignty and the enforcement of International Criminal Court (ICC) judgments arises when states perceive that the implementation of these judgments harms their sovereignty or diminishes their power and jurisdiction. Although in the 19th century, states voluntarily granted the Court jurisdiction to prosecute international crimes to establish international order, security, and peace in their relations, some countries consider the enforcement of ICC judgments to be contrary to their interests and thus do not implement them. Therefore, examining the conflict between the principle of state sovereignty and the enforcement of the Court's judgments is crucial in the international arena. Ensuring international order and security necessitates research on such a topic. The objective of this research is to identify the interveners in international order concerning the enforcement of the Court's judgments, in order to determine their conflict or interaction with the enforcement of ICC judgments. The present study, by examining the principles of state sovereignty and the jurisdiction of the International Criminal Court, employs a descriptive-analytical method and utilizes library and internet resources to answer the question of whether the enforcement of the Court's judgments conflicts with the principle of state sovereignty. The research findings indicate that the enforcement of the Court's judgments is not only not contrary to state sovereignty but is also essential for respecting human rights and maintaining international order. States that do not act in accordance with the Statute and judgments of the Court do so due to their pursuit of power, economic interests, and the preservation of their political ideologies in interactions with other countries.